PROBLEMS AND SPECIFICS OF FOREIGN MADE AIRCRAFT AVIONICS SYSTEMS OPERATION IN THE EXTREMELY LOW TEMPERATURE CONDITION OF SIBERIA, YAKUTIA AND NOTHERN REGIONS - V. P. Gorbunov (Naučnyj Vestnik MGTU GA, 2016)
The article describes problems and peculiarities of aircraft Cold Weather operation in Siberia’s Northern areas, highlighting the difficulties to maintain the aircraft Avionics system functionality, providing the required level of safety and reliability at very low temperatures environment.